Mechanical properties of the as-cast quartz particulate reinforced LM6 alloy matrix composites - Sulaiman, Shamsuddin; Mohd Sayuti,; Samin, Razali (Elsevier, 2008)
Metal matrix composites are engineered materials combining two or more materials, one of which is a metal, where the tailored properties can be attained by systematic combination of different constituents. A variety of methods available for producing these advanced materials include the conventional casting process which is considered as the easiest processing technique. Preparation of these composite materials by foundry technology has the unique benefit of near-net shape fabrication in a simple and cost-effective manner. Besides, casting processes lend themselves to manufacture large number of complex shaped components of composites at a faster rate required by the automotive, transportation, sports and other consumer oriented industries. In this study, quartz–silicon dioxide particulate reinforced LM6 alloy matrix composites were fabricated by carbon dioxide sand molding process by varying the particulate addition by volume fraction on percentage basis. Tensile and hardness tests and scanning electron microscopic studies were conducted to determine the maximum load, tensile strength and modulus of elasticity. Hardness values are measured for the quartz particulate reinforced LM6 alloy composites and it has been found that it gradually increases with the increased in addition of the reinforcement phase. The tensile strength of the composites decreases with the increased in addition of quartz particulate. The fractographs taken after the tensile test illustrates the particle pullout from the matrix due to lack of bonding and load deformation characteristic mechanism.